Потенціал використання систем моделювання при розробці державних заходів із фінансово-економічного стимулювання розвитку смарт-промисловості - Okhten, Oleksiy O.; Dasiv, Alla F. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The article presents the constituent elements of the system of financial and economic stimulation of the development of smart industry (and scientific and technological progress in general), the main of which are defined as monetary (monetary and credit) and fiscal (tax and budget) stimulation.The results of the analysis of the currently existing economic modeling software systems, which can be used to determine directions for stimulating the development of smart industry, are given. Such modeling software products included: "Energy Policy Simulator" system by the Energy Innovation Policy & Technology Institute, “Siforeca” industrial forecasting and foresight system by the Institute of Industrial Economics of the National Academy of Sciences of Ukraine, Global Industry Model by Oxford Economics consulting company, the Global Economic Data & Forecasts system from Moody's Analytics consulting company.Features of governmental practical measures of foreign countries for the financial and economic stimulation of the development of smart industry are also given, which include: the EU Industrial Research and Development Investment Scoreboard; Inflation Reduction Act (USA); the New Industrial Strategy of the EU; practical mechanisms for stimulating smart industry in China; Japan's government initiatives to stimulate the development of smart industry.The analysis of the policies for stimulating the development of smart industry in the countries and regions that are leaders in this area (the USA, the EU, China and Japan) made it possible to establish that there is fierce competition between the leading countries – they are trying to secure leading positions in the field of specific technologies and the market as a whole. The main tools for stimulating the development of smart industry are direct financial injections (from dedicated governmental funds) and tax benefits. The development of smart industry is closely intertwined with the environmental agenda, and governments are trying to direct investments in advanced technologies in environmental areas. The leading countries do not wait for market mechanisms to distribute investments in smart industry on their own, but make targeted efforts to stimulate such investments. The modeling tools can be used (and is already used) at all stages of the development and implementation of measures for financial and economic stimulation of the development of smart industry – ranging from the selection of a specific stimulation tools to the determination of the volume of stimulation measures and directions of their application.